Corrosion behavior of borate modified Hench’s bioglasses containing dopant cobalt oxide - Abdou, Y.; M. Abdelghany, A.; El-gendy, A.; A. El-Husseiny, F. (International Journal of Basic and Applied Sciences, 2021)
Cobalt doped modified borophosphate glasses similar to Henchâ€™s bioglass were successfully synthesized using gradually increasing cobalt ions in addition to another sample of Co free glass. Synthesized samples were studied for their bioactivity through immersion in phosphate solution for different time intervals. FTIR absorption spectral data were collected before and after immersion for a prolonged time intervals. Spectral data reveals appearance of absorption band at 573 cm-1 Splitted into 565 cm-1 and 603 cm-1 after one week of immersion supporting the bone bonding ability and biocompatibility with bone. The change in the calculated N4 value also indi-cate the conversion of both BO3 and BO4 strutural units associated with the formation of hydroxyapatite. Magnetic characteristics meas-ured and calculated through VSM measurements supporting the idea of using such material as a bioactive material that can be used in hyperthermia treatment. Â Â